Genetic variation in the serotonin transporter and HTR1B receptor predicts reduced bone formation during serotonin reuptake inhibitor treatment in older adults. (July 2014) - Garfield, Lauren D.; Müller, Daniel J.; Kennedy, James L.; Mulsant, Benoit H.; Reynolds, Charles F.; Teitelbaum, Steven L.; Civitelli, Roberto; Dixon, David; Todorov, Alexandre A.; Lenze, Eric J.
Abstract Objectives. Studies have reported an association between serotonin reuptake inhibitors (SRIs) and accelerated bone loss. Genetic variation in the serotonin system might modulate bone metabolism changes during SRI treatment. In a clinical trial we examined functional genetic polymorphisms of serotonin transporter and receptors involved in bone metabolism to determine whether they predict changes in bone metabolism during SRI treatment. Methods. In 69 adults (age ≥ 60) participating in a 12-week, open-label trial of the SRI venlafaxine for major depression, serum markers of bone formation (P1NP) and resorption (β-CTX) were assayed before and after treatment. Participants were genotyped for putative high- versus low-expressing polymorphisms in the serotonin transporter (5HTTLPR) and 1B receptor (HTR1B) genes. Results. Bone formation was significantly reduced with administration of venlafaxine in participants with the high-expressing 5HTTLPR genotype and those with the low-expressing HTR1B genotype. This primarily occurred in individuals with the combination of the high-expressing 5HTTLPR genotype and the low-expressing HTR1B genotype. Conclusions. These preliminary findings indicate that genetic variation in the serotonin receptors predicts changes in bone metabolism during SRI use. If these results are replicated and clinically confirmed, we will have identified a genetic subgroup at high risk for deleterious bone outcomes with the use of SRIs.